QUIZZIZ ONLINE APPLICATION AS APPLICATION AS A PLEASANT LEARNING SOLUTION IN THE PANDEMIC PERIOD - Roysa, Mila; Hartani, Anisa (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study is to describe alternatives to joy fun online learning using the quizziz application. The research method used is qualitative research. The study was conducted at vocational high school Miftahul Falah, Dawe District, Kudus Regency. Acquisition of data results using indept interviews sent via googleform and key informants to teachers dan students. Based on the results of the study it was concluded that (1) quizziz online learning application is a technology based learning evaluation application that can be accessed online by teachers and students, which is applied during a pandemic in the education sector in order to be able to balance and harmonize learning in school to be always relevant and enjoyable especially in Indonesian language learning content; (2) the existence of the quizziz application provides alternative online learning that can be done without having to face to face directly between the teacher and students and can be accessed outside and in the classroom; (3) quizziz provides advantages for online learning by utilizing learning changes that prioritize learning in the era of the industrial revolution 4.0 using information technology in its delivery, will be more fun, motivating, and attracting the attention of students. Thus, the use of quizziz can make the implementation of online learning no longer make a problem for students and is flexible in accordance with students abilities.